Prevalence of dental caries in children aged 6 and 12 in a district of the province of Islay, Arequipa - Lavado García, Mayra Isaura (2024)
Objective: To determine the prevalence of caries using the CEOD and CPOD indices and compare them according to sociodemographic characteristics in children aged 6 and 12 years in a district of the province of Islay, Arequipa. Material and methods: Relational, cross-sectional, prospective, cross-sectional study. After informed parental consent, 50 children underwent an oral examination, using the CEOD index for 6-year-old children and CPOD for 12-year-old children, who participated in an educational program in the year 2023. These data were recorded in individual files and then processed in the SPSS program. Descriptive statistics and Chi2 test were used for the analysis. Results: Of the total number of children, 56 % were female and 52 % were 12 years old. The prevalence of caries was high in 28 % and very high or moderate in 22 %. According to gender, 32.1 % of the girls had a high caries index and 21.4 % had high or moderate caries, while 22.7 % of the boys had moderate, high or very high caries. According to age, in children 6 years old, the presence of low, moderate, high and very high categories was 25 % for all cases; while in children 12 years old, the high category was the most frequent in 30.8 %. Conclusion: When considering the sociodemographic characteristics of the children, no significant differences were found in the prevalence of caries according to gender or age.